General Influence Coefficient Algorithm in Balancing of Rotating Machinery - Xiaoping Yu (International Journal of Rotating Machinery)
The General Influence Coefficient Algorithm (GICA), developed in this article, is a new calculation method for Influence Coefficients (ICs) with a general formula. Compared to the traditional calculation method, GICA can solve the ICs' calculation task when the group of trial weights are installed on the rotor each time, the trial weights are retained on the rotor systems, or there is redundant trial balancing data, when even part of the ICs is known. GICA is also a powerful tool for refining the ICs from redundant balancing data or historical balancing data and serves as a general algorithm. With the general matrix formula, GICA is ready to be applied in a computer-aided balancing system as the key part of calculation software. Examples in industry are also presented to demonstrate the aplication of this new algorithm.